Analysis and Research of the Generating Plane Inclination Angle of the Plane Enveloping Internal Meshing Worm Drive - Feng Zhipeng; Deng Xingqiao; Jiang Yuanyuan; Zhang Pan (Jixie chuandong, 2017)
The generating plane inclination angle has a great influence on the meshing performance of the plane enveloping internal meshing worm drive,and it has a decisive role in determining the optimal parameters of the plane enveloping internal meshing worm transmission. Based on the principle of gear meshing,the worm tooth surface contact and the induced curvature equation are constructed,by using the numerical calculation method and the Hertz contact stress calculation model,the influence of worm wheel tooth number and center distance change on the plane enveloping internal meshing worm drive under the condition of the single head plane enveloping internal meshing worm drive is analyzed. The study demonstrates that the meshing performance of the plane enveloping internal meshing worm when the generating plane inclination angle is in the range of 18°to 36° is better than that of other angles. The research results lay the theoretical foundation for the follow-up study of the plane enveloping internal meshing worm gearing drive.